Clinical Trials in Family Practice - Roy Jobson (South African Family Practice)
At some stages of their careers many Family Physicians and General Practitioners will be approached by a pharmaceutical company or a 'clinical research organisation' (CRO) to be an investigator in a clinical trial. According to the South African Clinical Trials Guidelines 2000; a clinical trial is '[a]ny investigation in human subjects intended to discover or verify the clinical, pharmacological and/or other pharmacodynamic effects of an investigational product[s], and/or to identify any adverse reactions to an investigational product[s], and/or to study absorption, distribution, metabolism, and excretion of an investigational product[s] with the object of ascertaining its safety and/or efficacy.